Electrochemical sensors based on gold nanoparticles and nanocomposite of MWCNT-OH/graphene for detecting hydrazine and nitrite simultaneously - Wulan Tri Wahyuni; Hemas Arif Rahman; Rayyan Azzahra Hidayat; Asmi Aris; Munawar Khalil; Chika Takai-Yamashita; Budi Riza Putra (Next Materials)
A straightforward method was introduced for the simultaneous measurement of hydrazine and nitrite using a composite of hydroxylated multiwalled carbon nanotubes (MWCNT-OH) and graphene decorated with gold nanoparticles (AuNPs) deposited on the surface of a glassy carbon electrode (GCE). Chitosan nanofibers were used as a capping agent for the preparation of AuNPs, which were subsequently immobilized on the surface of the MWCNT-OH/graphene composite. The morphological structure and physical properties of the AuNPs/MWCNT-OH/graphene composite were characterized using several advanced instrumentation techniques, with its electroanalytical performance being optimized using the differential pulse voltammetry method. It was found that the synergistic work between AuNPs and the composite of MWCNT-OH/graphene provides enhanced electrocatalytic activity, leading to higher conductivity for the simultaneous detection of hydrazine and nitrite at pH 7. The proposed sensor also exhibits a clear separation of both anodic peaks, showing a linear current response within concentration ranges of 0.04–1 mM for hydrazine and 0.02–0.9 mM for nitrite. Thus, it can be calculated that the detection limit for hydrazine and nitrite was 4.11 and 3.64 µM, respectively. Moreover, the suggested sensor exhibited excellent reproducibility and stability in detecting hydrazine and nitrite simultaneously, with good selectivity indicated by percentage recovery values ranging from 97 % to 112 %. The suggested sensor was also effectively utilized to detect hydrazine and nitrite simultaneously in tap and lake water samples, which might pave the way for its development as an alternative method for pollutant detection in the water environment.